2022
DOI: 10.1109/lsp.2022.3185964
|View full text |Cite
|
Sign up to set email alerts
|

Privacy-Phys: Facial Video-Based Physiological Modification for Privacy Protection

Abstract: The invisible remote photoplethysmography (rPPG) signals in facial videos can reveal the cardiac rhythm and physiological status. Recent studies show that rPPG is a noncontact way for emotion recognition, disease detection, and biometric identification, which means there is a potential privacy problem about physiological information leakage from facial videos. Therefore, it is essential to process facial videos to prevent rPPG extraction in privacy-sensitive situations such as online video meetings. In this le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In daily life and work, there is a potential privacy problem with the leakage of physiological information, including physiological signals and facial expressions. Sun and Li [100] presented a new approach based on a pre-trained 3D convolutional neural network, i.e., Privacy-Phys, to modify remote photoplethysmography in facial videos for privacy. The results showed that the approach was more effective and efficient than the previous baseline.…”
Section: Ethical and Privacy Concerns Related To The Use Of Physiolog...mentioning
confidence: 99%
“…In daily life and work, there is a potential privacy problem with the leakage of physiological information, including physiological signals and facial expressions. Sun and Li [100] presented a new approach based on a pre-trained 3D convolutional neural network, i.e., Privacy-Phys, to modify remote photoplethysmography in facial videos for privacy. The results showed that the approach was more effective and efficient than the previous baseline.…”
Section: Ethical and Privacy Concerns Related To The Use Of Physiolog...mentioning
confidence: 99%
“…For example, in PulseEdit [88], a novel security algorithm capable of editing physiological signals to conceal a person's cardiac activity and physiological status without altering or distorting the original visual appearance was proposed to protect the user's physiological signal from being disclosed. Similarly, Sun et al [89] proposed PrivacyPhys, a model that modifies rPPG in facial videos captured from online video meetings or video-sharing platforms in order to safeguard against malicious capture and ensure privacy.…”
Section: Gaps and Influencing Challengesmentioning
confidence: 99%
“…[ 123 ] But it was only tested on simple datasets, which may be not suitable for realistic situations such as sudden facial expressions. To address the aforementioned problems, Sun et al [ 124 ] presented a novel method called Privacy‐Phys on the basis of a pretrained 3D convolutional neural network, to modify rPPG signal in facial videos, in which the modified video is visibly similar to the original video. Future works should pay more attention to privacy‐preserving techniques for personal information protection.…”
Section: Future Prospectsmentioning
confidence: 99%